Beyond pseudo-rotations in pseudo-euclidean spaces : an introduction to the theory of bi-gyrogroups and bi-gyrovector spaces - Ungar, Abraham A. (Mathematical analysis and its applications., 2018)
Beyond Pseudo-Rotations in Pseudo-Euclidean Spaces presents for the first time a unified study of the Lorentz transformation group SO(m, n) of signature (m, n), m, n? N, which is fully analogous to the Lorentz group SO(1, 3) of Einstein's special theory of relativity. It is based on a novel parametric realization of pseudo-rotations by a vector-like parameter with two orientation parameters. The book is of interest to specialized researchers in the areas of algebra, geometry and mathematical physics, containing new results that suggest further exploration in these areas.